2023
DOI: 10.1101/2023.06.28.546852
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hepatoblastoma exhibits a predominantly myeloid immune landscape and reveals opportunities for macrophage targeted immunotherapy

Daniëlle Krijgsman,
Lianne Kraaier,
Meggy Verdonschot
et al.

Abstract: Background & Aims: Hepatoblastoma (HB) is a rare form of pediatric liver cancer which is currently treated with chemotherapy and surgery. The side effects of chemotherapy pose a major problem in HB and underline the need for an alternative treatment option. We aimed to characterize the immune landscape of HB to improve our understanding of the immunologic contribution to this disease and explore immunotherapeutic options. Methods: An imaging mass cytometry panel of 36 antibodies was used on tissue of treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…A recent publication showed that chemotherapy increased influx of TAMs and CD8 + T-cells in the HB-treated group. 7 On the other hand, our recent studies showed that chemotherapeutics induced overexpression of immunosuppressive IL-32 22 and SerpinB9 26 in different HB cell lines, which might be included in tumor invasion and chemoresistance. Thus, the abovementioned crosstalk is not a mere dual conversation between TAMs and HB in an isolated TME, but a multifactorial noise.…”
Section: Effect Of Therapeutic and Nontherapeutic Chemicals On Hb Tmementioning
confidence: 97%
See 4 more Smart Citations
“…A recent publication showed that chemotherapy increased influx of TAMs and CD8 + T-cells in the HB-treated group. 7 On the other hand, our recent studies showed that chemotherapeutics induced overexpression of immunosuppressive IL-32 22 and SerpinB9 26 in different HB cell lines, which might be included in tumor invasion and chemoresistance. Thus, the abovementioned crosstalk is not a mere dual conversation between TAMs and HB in an isolated TME, but a multifactorial noise.…”
Section: Effect Of Therapeutic and Nontherapeutic Chemicals On Hb Tmementioning
confidence: 97%
“…14 IL-34, which is another ligand of M-CSFR, was found to be expressed in the tumor cells of the embryonal and recurrent HB as well, and thought to be associated with tumor cell proliferation, chemoresistance, and TAMs infiltration. 13 Krijgsman et al 7 also showed that TAMs infiltrating the resected HB specimens lack the expression of the Kupffer cell marker (MARCO), suggesting that HB TAMs are monocyte-derived cells, rather than embryonic-derived macrophages. Furthermore, TAMs express myeloid checkpoint molecules such as CD47, SIRPα, and VISTA, making their targeting possible, unlike T-cells that lack the mentioned molecules' expression.…”
Section: Protumor Phenotypes Of Tams In Hbmentioning
confidence: 99%
See 3 more Smart Citations